Complementary actions - Sartori, Luisa; Betti, Sonia (Frontiers in Psychology, 2015)
Complementary colors are color pairs which, when combined in the right proportions, produce white or black. Complementary actions refer here to forms of social interaction wherein individuals adapt their joint actions according to a common aim. Notably, complementary actions are incongruent actions. But being incongruent is not sufficient to be complementary (i.e., to complete the action of another person). Successful complementary interactions are founded on the abilities: (i) to simulate another person’s movements, (ii) to predict another person’s future action/s, (iii) to produce an appropriate incongruent response which differ, while interacting, with observed ones, and (iv) to complete the social interaction by integrating the predicted effects of one’s own action with those of another person. This definition clearly alludes to the functional importance of complementary actions in the perception–action cycle and prompts us to scrutinize what is taking place behind the scenes. Preliminary data on this topic have been provided by recent cutting-edge studies utilizing different research methods. This mini-review aims to provide an up-to-date overview of the processes and the specific activations underlying complementary actions.